IL-6 receptor inhibition with tocilizumab improves treatment outcomes in patients with rheumatoid arthritis refractory to anti-tumour necrosis factor biologicals: results from a 24-week multicentre randomised placebo-controlled trial. Issue 11 (14th July 2008) - Emery, P; Keystone, E; Tony, H P; Cantagrel, A; van Vollenhoven, R; Sanchez, A; Alecock, E; Lee, J; Kremer, J
Abstract : Objectives: The phase III RADIATE study examined the efficacy and safety of tocilizumab, an anti-IL-6 receptor monoclonal antibody in patients with rheumatoid arthritis (RA) refractory to tumour necrosis factor (TNF) antagonist therapy. Methods: 499 patients with inadequate response to one or more TNF antagonists were randomly assigned to receive 8 mg/kg or 4 mg/kg tocilizumab or placebo (control) intravenously every 4 weeks with stable methotrexate for 24 weeks. ACR20 responses, secondary efficacy and safety endpoints were assessed. Results: ACR20 was achieved at 24 weeks by 50.0%, 30.4% and 10.1% of patients in the 8 mg/kg, 4 mg/kg and control groups, respectively (less than p<0.001 both tocilizumab groups versus control). At week 4 more patients achieved ACR20 in 8 mg/kg tocilizumab versus controls (less than p = 0.001). Patients responded regardless of most recently failed anti-TNF or the number of failed treatments. DAS28 remission (DAS28 <2.6) rates at week 24 were clearly dose related, being achieved by 30.1%, 7.6% and 1.6% of 8 mg/kg, 4 mg/kg and control groups (less than p = 0.001 for 8 mg/kg and p = 0.053 for 4 mg/kg versus control). Most adverse events were mild or moderate with overall incidences of 84.0%, 87.1% and 80.6%, respectively. The most common adverse events with higher incidence in tocilizumab groups were infections, gastrointestinal symptoms, rash and headache. The incidence of serious adverse events was higher in controls (11.3%) than in the 8 mg/kg (6.3%) and 4 mg/kg (7.4%) groups. Conclusion: Tocilizumab plus methotrexate is effective in achieving rapid and sustained improvements in signs and symptoms of RA in patients with inadequate response to TNF antagonists and has a manageable safety profile. Trial registration number: NCT00106522.